2013
DOI: 10.1177/0883073813511150
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Responses to Various Visual Stimuli in Children With Visual Processing Impairments or Infantile Nystagmus Syndrome

Abstract: Quantification of orienting responses can be used to differentiate between children with cerebral visual impairment and infantile nystagmus syndrome. To further improve the sensitivity of this method, we compared orienting responses to a Cartoon stimulus, which contains all sorts of visual information, to stimuli that contain only Contrast, Form coherence, Motion coherence, Color and Motion detection. The stimuli were shown on an eye tracker monitor using a preferential looking paradigm. We found that both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…In addition, children with nystagmus have lower fixation accuracy than children without nystagmus but with other types of visual impairment (mean difference = 0.71º; t = 5.03, p <0.001; Cohen's d = 1.04). This is consistent with previously published findings on GFA in subgroups of the present dataset 20,24,25 . …”
Section: Quantitative Analysis Of Eye Movementssupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, children with nystagmus have lower fixation accuracy than children without nystagmus but with other types of visual impairment (mean difference = 0.71º; t = 5.03, p <0.001; Cohen's d = 1.04). This is consistent with previously published findings on GFA in subgroups of the present dataset 20,24,25 . …”
Section: Quantitative Analysis Of Eye Movementssupporting
confidence: 94%
“…Although we limited ourselves to the presentation of results from cartoon stimuli, in future applications different visual modalities can be tested using other stimuli (e.g., distinct forms, motion, color and contrast information) 22,20,25 . That way, specific visual processing areas beyond the primary visual pathways are targeted, such as visual association areas in temporal or parietal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In the reference group we do not see a decrease in response time for motion. This stimulus might be more difficult to detect for children with visual (processing) impairments, who have slower response times and larger fixation areas for this stimulus than typically developing children, in this study and a previous one (Pel et al, 2013). These difficulties should be taken into account in future applications of this method, for example by providing a practice session before the start of the measurement.…”
Section: Reliability and Criterion For Response Timesmentioning
confidence: 79%
“…Previous research showed that children with CVI had slower orienting responses to a variety of visual stimuli than typically developing children and than children with ocular motor impairments (Pel et al, 2010b(Pel et al, , 2013. The slower orienting responses could not be explained by other types of visual impairments, i.e.…”
Section: Introductionmentioning
confidence: 81%
“…3,22 Training-induced acuity improvements might thus be related to prolonged foveation periods after training. Saccade latencies are also longer for individuals with IN compared with individuals with normal vision (NV), 17,23 which might explain the longer visual search times in children with IN. [24][25][26] Faster saccade initiation and improved landing position would particularly facilitate visual performance on tasks with time restrictions, such as our training tasks, since it would bring the target longer and closer to the center of the fovea.…”
mentioning
confidence: 99%